THE ROLE OF ZAKAT ON ADDRESSING POVERTY REDUCTION IN YOBE STATE - YAKASAI, MUSA UMAR; JIBRIN, MUNUBIYYAH SANI; ZANNA, LAWAN ALI (Innovare Journal of Social Sciences, 2021)
Poverty has become paramount, and it is been given much emphasis in different aspects since the declaration and introduction of the Zakat institutions in Yobe State Nigeria. The declaration focuses strongly on the reduction of state poverty within the recent activities of Islamic Financial Institutions as Islam provides an essential tool to completely prove in reducing poverty. The objective of the study is to assess the role of Zakat in addressing some levels of poverty reduction in Yobe State, Nigeria. A survey was conducted within 17 local governments of Yobe State, in which 20 questionnaires were served to each local government with total of 340. The study employed factor analysis for assessing the relation between the variables adopted, and descriptive and independent t-test analyses are considered for the analyses. The result shows that the Zakat has played a significant role in addressing poverty reductions in Yobe State, Nigeria.